Improving the U.S. military's understanding of unstable environments vulnerable to violent extremist groups : insights from social science - Thaler, David E. (RAND, 2013)
For over a decade, operations associated with irregular warfare have placed large demands on U.S. ground forces and have led to development of new Army and Joint doctrine. This report helps analysts identify and assess twelve key factors that create and perpetuate environments susceptible to insurgency, terrorism, and other extremist violence and instability to inform military decisions on allocation of analytic and security assistance resources.